Pemetaan konflik di Provinsi Maluku - Pariella, Tonny D.; B. Saija, Dominggus E.; Frans, Jouverd F.; Pesurnay, Charles; Alfons, Christwyn (ppjbsip, 2023)
This research aims to map the types of conflicts that occurred in Maluku Province. Data had collected through interviews, recording techniques, and secondary sources in books, newspapers, reports, and media coverage. The study results show that the Maluku conflicts are generally related to socio-cultural aspects because the problem of petuanan land boundaries and differences in views about adat are still the main causes. The general type of conflict is external/horizontal because it occurs between neighboring countries or villages and only involves community groups. It is manifest (open) due to physical contact and mutual attacks between community members. Apart from the conflict due to cultural aspects, other aspects also contributed to the conflict in Maluku, namely the economic aspect. The economic aspect arises because of competition to meet the needs of life. AbstrakTujuan penelitian ini adalah memetakan jenis-jenis konflik yang terjadi di Provinsi Maluku. Data dikumpulkan melalui teknik wawancara dan perekaman serta ditunjang dengan sumber sekunder berupa buku, koran, laporan, dan pemeberitaan di media. Hasil penelitian menunjukkan bahwa konflik Maluku umumnya terkait dengan aspek sosial budaya karena masalah batas tanah petuanan dan perbedaan-perbedaan pandangan tentang adat masih menjadi penyebab pokok. Jenis konflik umumnya, eksternal/horisontal karena terjadi antara negeri-negeri atau desa-desa bertetangga dan hanya melibatkan kelompok-kelompok masyarakat dan bersifat manifes (terbuka) karena adanya kontak fisik dan saling menyerang antar warga masyarakat. Selain konflik dikarenakan aspke budaya, aspek lainnya juga turut membentuk konflik di Maluku, yakni aspek ekonomi. Aspek ekonomi muncul karena adanya persaingan dalam upaya memenuhi kebutuhan hidup.